Role of leukocyte parameters in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention with high thrombus burden - Wang, Hao; Li, Shixing; Yu, Jin; Xu, Jingsong; Xu, Yan (Frontiers in Cardiovascular Medicine, 2024)
Objective: Leukocyte parameters were associated with cardiovascular diseases. The aim of present study was to investigate the role of leukocyte parameters in ST-segment elevation myocardial infarction (STEMI) patients underwent primary percutaneous coronary intervention (PPCI) with high thrombus burden (HTB).Methods: A total of 102 consecutive STEMI patients with HTB who underwent PPCI within 12h from the onset of symptoms from June 2020 to September 2021 were enrolled in this study. And 101 age-and sex-matched STEMI patients with low thrombus burden (LTB) underwent PPCI within 12h from the onset of symptoms as controls. Leukocyte parameters such as neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and monocyte to lymphocyte ratio (MLR) were calculated at the time of admission.Results: The value of NLR and MLR were significantly higher in HTB group than